Environmental Problems and the Question of Intergenerational Justice from the Kantian Perspective - Timothy Adie OKPE; Samuel Akpan BASSEY (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
In this paper, I aim at unraveling some of the numerous environmental practices in Nigeria that often times leads to environmental degradation which to a larger extent affects us presently and the effect on the future generation is better imagined if positive actions are not taken to check this trend. It is on the basis of this using one of Kant's categorical imperative that states that "we should act only on that maxim that you can will as a universal law" will be used as the main focus of this paper to bring to bear or light that, we actually owe the future generation the duty to conserve the environment for them. This work argues that we should be careful and considerate with the way we treat the environment through our actions because if the generation before ours had abuse and degrade the environment the way we are doing, our present generation would not have had a beginning. It is my humble submission that this can be achieved through radical exposure to the harm done on the ecosystem by this present generation and a radical awareness that will be taken to the very foundation of our grass root. It is only just and fair that this present generation stop the misuse of the environment. This justice if pursued will go ahead to preserve and conserve the environment for the future generation. The method used basically is systematic analysis, expository, argumentative and critical thinking to enable me make valid and acceptable judgment.